2007
DOI: 10.3168/jds.s0022-0302(07)72634-6
|View full text |Cite
|
Sign up to set email alerts
|

Interventions After Artificial Insemination: Conception Rates, Pregnancy Survival, and Ovarian Responses to Gonadotropin-Releasing Hormone, Human Chorionic Gonadotropin, and Progesterone

Abstract: We hypothesized that increasing concentrations of progesterone (P4) after artificial insemination would increase fertility. Our objective was to assess changes in ovarian structures, incidence of ovulation, and change in serum P4 in response to GnRH, human chorionic gonadotropin (hCG), or exogenous P4 (controlled internal drug release; CIDR insert) treatment beginning 4 to 9 d after artificial insemination (d 0) and again 7 d later (experiment 1). Blood was collected from 753 cows in 3 herds on d 0 and 7. Ovar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
88
3
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(111 citation statements)
references
References 27 publications
14
88
3
6
Order By: Relevance
“…However, circulating P4 remained lower, even after hCG treatment, in lactating cows compared with normally ovulating heifers. Eight studies that evaluated the effect of hCG on P4 concentrations from days 4 to 7 after AI in lactating dairy cows reported significant increases in circulating P4 concentrations after treatments with different doses of hCG: 3300 IU (Schmitt et al, 1996;Santos et al, 2001), 2500 IU (Stevenson et al, 2007b;Vasconcelos et al, 2011); 1500 IU (Walton et al, 1990;Hanlon et al, 2005; Kendall et al, 2009) or 1000 IU (Rajamahendran and Sianangama, 1992). Thus, treatment with hCG on day 5 after AI produces a consistent, fairly rapid (3 days delay) increase in circulating P4 in lactating dairy cows.…”
Section: Importance Of High P4 After Aimentioning
confidence: 99%
See 2 more Smart Citations
“…However, circulating P4 remained lower, even after hCG treatment, in lactating cows compared with normally ovulating heifers. Eight studies that evaluated the effect of hCG on P4 concentrations from days 4 to 7 after AI in lactating dairy cows reported significant increases in circulating P4 concentrations after treatments with different doses of hCG: 3300 IU (Schmitt et al, 1996;Santos et al, 2001), 2500 IU (Stevenson et al, 2007b;Vasconcelos et al, 2011); 1500 IU (Walton et al, 1990;Hanlon et al, 2005; Kendall et al, 2009) or 1000 IU (Rajamahendran and Sianangama, 1992). Thus, treatment with hCG on day 5 after AI produces a consistent, fairly rapid (3 days delay) increase in circulating P4 in lactating dairy cows.…”
Section: Importance Of High P4 After Aimentioning
confidence: 99%
“…Of the 30 trials that we evaluated, the vast majority (25/30) showed a numeric improvement in fertility with P4 supplementation, although only six of these trials showed significance (P < 0.05). Only two (Stevenson et al, 2007b;Nascimento et al, 2013c) of these trials that found significance used >100 animals per comparison.…”
Section: Importance Of High P4 After Aimentioning
confidence: 99%
See 1 more Smart Citation
“…In general, it is thought that stimulation of embryo development by an early rise in progesterone should benefit fertility (STRONGE et al, 2005;PARR et al, 2012), possibly because of advancing conceptus development. Nevertheless, fertility responses to exogenous progesterone seem to be greater when supplementation occurs before than after (STEVENSON et al, 2007) AI. In most studies with post-AI progesterone supplementation to lactating dairy cows no apparent attempt was made to mimic the normal rise in progesterone observed in heifers, which is greater and faster than that of cows ).…”
Section: Introductionmentioning
confidence: 97%
“…It is thought that inadequate progesterone concentrations during early development of the conceptus might be one of the reasons for reduced fertility observed in high-producing dairy cows (WILTBANK et al, 2011), in part because catabolism of steroids increases with increased feed intake associated with high production WILTBANK et al, 2011). In fact, supplemental progesterone after AI from an exogenous source (STEVENSON et al, 2007;WILTBANK et al, 2011) Timed AI protocols result in variable sizes of ovulatory follicles in dairy cows SANTOS et al, 2010). Induction of ovulation of small follicles resulted in reduced P/AI in beef (PERRY et al, 2005) and dairy cows , and increased risk of pregnancy loss (PERRY et al, 2005).…”
Section: Introductionmentioning
confidence: 99%